ELF3 promotes epithelial–mesenchymal transition by protecting ZEB1 from miR-141-3p-mediated silencing in hepatocellular carcinoma. Issue 3 (March 2018) - Zheng, Longbo; Xu, Ming; Xu, Junjie; Wu, Ke; Fang, Qian; Liang, Yuelong; Zhou, Senjun; Cen, Dong; Ji, Lin; Han, Weili; Cai, Xiujun
Abstract Hepatocellular carcinoma (HCC) is one of the most common malignant cancers and currently the third leading cause of cancer-related deaths, worldwide. Epithelial–mesenchymal transition (EMT) plays a major role in HCC progression. In this study, we first found that the expression of E74-like ETS transcription factor 3 (ELF3), a member of the E-twenty-six family of transcription factors, was increased in HCC tissues, and that ELF3 overexpression was associated with poor prognoses for HCC patients. Gain-of-function and loss-of-function studies revealed that increased ELF3 expression promoted HCC cell proliferation, migration, and invasion, while these processes were inhibited when ELF3 was silenced. Additionally, ELF3 was found to promote EMT, which we demonstrated through decreased E-cadherin expression and increased N-cadherin and fibronectin expression. ELF3 knockdown reversed EMT via repressing ZEB1 expression through miR-141-3p upregulation. Chromatin immunoprecipitation assays revealed that ELF3 bound to the miR-141-3p promoter, suppressing miR-141-3p expression. Taken together, our data show that ELF3 repressed E-cadherin and promoted EMT in HCC cells by suppressing miR-141-3p, thereby activating ZEB1. Thus, ELF3 may be a potential prognostic biomarker and/or therapeutic target for HCC.